Directions of production diversification and development of a sustainable economy based on a franchise mode - Nasimov Dilshodbek Hotam oglu; Khodjaev Anvar Rasulovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of the franchising model in economic diversification and sustainable development. The research findings indicate that franchising mechanisms strengthen economic stability by attracting foreign capital and advanced technologies, reducing market risks, mitigating regional economic disparities, and creating new jobs. At the same time, underdeveloped legal and institutional frameworks, limited access to financial resources, and insufficient managerial experience of local entrepreneurs are highlighted as key challenges. The study emphasizes that the implementation of franchising based on ESG (Environmental, Social, and Governance) standards is an essential factor in ensuring not only economic, but also ecological and social sustainability. Based on the results, practical recommendations are developed to support diversification through franchising in the context of Uzbekistan.